Penafsiran Hukum Waris Beda Agama di Indonesia - Mu’tashim Billah; Vivi Rahma (UIN Sunan Kalijaga Yogyakarta, 2021)
In classical fiqh studies, most scholars agree that Muslims and non-Muslims do not inherit from each other. Jumhur's opinion is stated implicitly in KHI, which says that heirs must be Muslim. After the 1995 Supreme Court decision regarding obligatory wills for heirs of different religions, differences of opinion began to occur over inheritance from different religions. Some follow this jurisprudence, while others still hold the jumhur opinion in classical fiqh. This article attempts to analyze the different interpretations of the regulations regarding heirs of different religions by using the theory of legal interpretation. This article is qualitative research with a normative juridical approach. The research data was obtained from various literature relevant to the object of this study. This article concludes that, in reading the regulations regarding heirs of different religions, there are three methods of legal interpretation, namely: first, a grammatical interpretation which results in the conclusion that non-Muslim heirs have no rights over the heir's assets; second, an analogical interpretation that can be used to make an analogy of a mandatory will for children or adoptive parents with the status of non-Muslim heirs; third, a sociological or teleological interpretation that functions more flexibly because it can be adapted to the context of social values that grow and develop in society.